Arteries of the Lower Limb—Embryology, Variations, and Clinical Significance. Issue 1 (February 2022) - Qazi, Emmad; Wilting, Joerg; Patel, Neeral R.; Alenezi, Abdullah O.; Kennedy, Sean A.; Tan, Kong T.; Jaberi, Arash; Mafeld, Sebastian
Objectives: The purpose of this article is to review the embryology of the lower limb arterial anatomy along with common variants and their clinical relevance. Design: Embryologic variations of the lower limb arterial system may be explained by i.) persistence of primordial arterial segments, ii.) abnormal fusion, iii.) segmental hypoplasia/absence, or a combination of both. Persistent sciatic artery, corona mortis, and popliteal entrapment syndrome will also be discussed with associated symptoms, and potential complications. Conclusion: Knowledge of these variations is essential for surgical and endovascular management as failure to recognize them can result in complications.